Morphological Features of Cell Death and Tissue Remolding of Fat Grafts. Issue 6 (June 2015) - Hao, Xiaoyan; Zhang, Teng; Yang, Yang; Feng, Hao; Wang, Yingmei; Song, Yajuan; Su, Yingjun; Guo, Shuzhong
Abstract : Background: Fat tissue graft has been commonly used for soft tissue augmentation. However, the mechanisms underlying the maintenance of graft volume and weight are still unclear. As morphological features provide direct evidences for cell death and survival, we aimed to investigate the fate of grafted adipocytes and the dynamic changes in the remodeling of adipose tissues by transmission electron microscopy technique. Methods: The unilateral inguinal fat pad of C57BL/6J mice was autografted to the dorsa of the mice. Perilipin expression and morphological changes were investigated by immunohistochemistry staining and transmission electron microscopy, respectively, in grafted tissues collected at posttransplantation days 0, 1, 3, 5, 7, 14, and 30. Results: Transmission electron microscopy analysis revealed that most adipocytes in grafts showed traits of cell death on postgrafting day 3. Multilocular adipocytes with naive nuclei were observed as early as day 5 and a larger number of multilocular adipocytes were found on day 14. Perilipin immunostaining revealed that only some adipocytes located in the margin of grafts survived through the ischemic injury. New adipocytes were visualized at the periphery of the grafts, although the scope of viable adipocyte zonal areas increased from day 5 to day 30. Conclusions: The results provide ultrastructural evidences associated with the remodeling dynamics of adipose tissue grafts. It is suggested that maximized volume of graft should be obtained through promoting regeneration other than improving survival of grafted adipose tissues.